Geological Structure Analysis to Determine the Direction of the Main Stress at Western Part of Kolok Mudik, Barangin District, Sawahlunto, West Sumatera - Jannah, Miftahul; Suryadi, Adi; Zafir, Muchtar; Saputra, Randi; Hakim, Ihsanul; Ariyuswanto, Riki; Yusti, Ulfa (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
On the study area there are three types of structure, those are fault, fold and joint. Types of fault were found  in the study area, reverse fault with the strike/dip is N215oE/75o, normal fault has a fault directions N22oE and N200oE with pitch 35o, and dextral fault with pitch 10o and strike N219oE. Fold and joint structures used to determine the direction of the main stress on the study area. Further, an analysis used stereonet for data folds and joints. So that from the data got three directions of main stress, those are Northeast â Southwest (T1), North â South (T2) and Southeast â Northwest (T3). On the Northeast â Southwest (T1) stress there are four geological structures, anticline fold at ST.3 , syncline folds at ST. 13a, ST. 13b, ST. 13c and ST. 33, chevron fold at ST. 44 and joint at ST. 2. On the North â South (T2) stress there are three geological structures, those are syncline fold at ST. 35, anticline fold at ST. 54 and joints at ST. 41, ST. 46 and ST. 47. On the Southeast â Northwest (T3) stress were also three geological structures, those are chevron fold at ST 42a, overturned fold at ST. 42b, syncline fold at ST. 42c and joints at ST. 5 and ST. 34.